Temporal Shifts in Microbial Communities in Nonpregnant African-American Women with and without Bacterial Vaginosis - Wertz, John; Isaacs-Cosgrove, Natasha; Holzman, Claudia; Marsh, Terence L. (Interdisciplinary Perspectives on Infectious Diseases, 2008)
Bacterial vaginosis (BV) has been described as an increase in the number of anaerobic and facultatively anaerobic bacteria relative to lactobacilli in the vaginal tract. Several undesirable consequences of this community shift can include irritation, white discharge, an elevated pH, and increased susceptibility to sexually transmitted infections. While the etiology of the condition remains ill defined, BV has been associated with adverse reproductive and pregnancy outcomes. In order to describe the structure of vaginal communities over time we determined the phylogenetic composition of vaginal communities from seven women sampled at multiple points using 16S rRNA gene sequencing. We found that women with no evidence of BV had communities dominated by lactobacilli that appeared stable over our sampling periods while those with BV had greater diversity and decreased stability overtime. In addition, only Lactobacillus iners was found in BV positive communities.